Antiskid Design Method and Simulation Optimization of Rope Rail Conveyors - Zhao Huijian; Zhang Yaocheng; Pang Xinyu; Zuo Lingfei; Tian Weiming (Jixie chuandong)
The rope rail conveyor has certain advantages over the belt conveyor in long-distance transportation, but the antiskid problem of its driving system has not been paid attention to. Combined with the structure of the driving wheel and transmission mode, an antiskid meshing pair is designed. Based on kinematics and high degree meshing contact theory, the load-bearing curve of a second-order contact antiskid meshing pair meeting the conditions of non-interference and strength, and the overall structure are designed. The second-order contact antiskid meshing pair and line contact antiskid meshing pair are modeled and simulated, and the sliding condition of the second-order contact antiskid meshing pair is tested by a single factor. The results show that the stress of the second-order contact antiskid meshing pair is more uniform than that of the line contact antiskid meshing pair; the curvature radius and height of antiskid bump of the antiskid meshing pair shall be smaller, and the width shall be larger.